CURRENT PRAGMATIC SITUATION OF INSURANCE BROKING IN LIFE INSURANCE IN UKRAINE - N. Tkachenko; O. Kryvytska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article investigates the practical aspects of the activity of insurance intermediaries in Ukraine. The structure and dynamics of insurance payments for life insurance in Ukraine as a whole, as well as in the context of residents and non-residents, are analyzed. The share of insurance intermediaries in the realization of life insurance services in Ukraine is revealed. The indexes of insurance intermediaries in the organization of life insurance in Ukraine for 2012-2016 are systematized. In the article mention that insurance intermediaries stay in not active phase in their activity in life insurance sphere. The definition of the insurance intermediary is defined in broad and narrow terms. The purpose of the activity of insurance intermediaries is determined. Schematically shows the common and excellent in the activities of the key representatives of insurance mediation - insurance agents and insurance brokers. It is argued that insurance intermediaries have the opportunity to become key players in life insurance, since they are the ones who can reach potential insurers in the shortest possible time. It is also noted that the further development of life insurance will largely depend on the professionalism of the insurance intermediary. Noted the appropriate identification of a life insurance intermediary with a financial advisor.